(untitled) (Journal of Computational Mathematics, 2021)
This paper discussed the number of zeros of the complex function F:C → C defined by F(Z)=_k=1^n(a_k cos(kZ)+b_k sin(kZ))+α_0+α_1 Im(z)+…+α_m(Im(Z))^m.